Reflections of a peacemaker : a portrait through heartsongs - Stepanek, Mattie J. T.; Stepanek, Jennifer Smith (Kansas City, Mo. : Andrews McMeel Pub., 2005)
Mattie J.T. Stepanek lived and died a child, but he had the spirit of a giant. Affected by a rare and fatal neuromuscular disease, Mattie lived almost fourteen years but in that time became a poet, best-selling author, peace activist, and a prominent voice for the Muscular Dystrophy Association. Before his death in June 2004, his five volumes of Heartsongs poetry sold more than a million copies. This is the final collection of Heartsongs that Mattie was working on when he died. In these poems he explores disability, despair, and death but also the gifts he finds in nature, prayer, peace, and his belief in something "bigger and better than the here and now."--Publisher description
Mosaic Heartsongs 1 -- Early Heartsongs 31 -- Festive Heartsongs 59 -- Stormy Heartsongs 83 -- Playful Heartsongs 109 -- Sacred Heartsongs 131 -- Tao de Heartsongs 155 -- Final Heartsongs 183 -- Epilogue: Eyes 207
Includes index.
Keywords: Children's writings, American; Muscular dystrophy -- Patients -- Poetry